Diesterified derivatives of 5-iodo-2'-deoxyuridine as cerebral tumor tracers. - Thomas W Rösler (Public Library of Science (PLoS), 2014)
With the aim to develop beneficial tracers for cerebral tumors, we tested two novel 5-iodo-2'-deoxyuridine (IUdR) derivatives, diesterified at the deoxyribose residue. The substances were designed to enhance the uptake into brain tumor tissue and to prolong the availability in the organism. We synthesized carrier added 5-[125I]iodo-3',5'-di-O-acetyl-2'-deoxyuridine (Ac2[125I]IUdR), 5-[125I]iodo-3',5'-di-O-pivaloyl-2'-deoxyuridine (Piv2[125I]IUdR) and their respective precursor molecules for the first time. HPLC was used for purification and to determine the specific activities. The iodonucleoside tracer were tested for their stability against human thymidine phosphorylase. DNA integration of each tracer was determined in 2 glioma cell lines (Gl261, CRL2397) and in PC12 cells in vitro. In mice, we measured the relative biodistribution and the tracer uptake in grafted brain tumors. Ac2[125I]IUdR, Piv2[125I]IUdR and [125I]IUdR (control) were prepared with labeling yields of 31-47% and radiochemical purities of >99% (HPLC). Both diesterified iodonucleoside tracers showed a nearly 100% resistance against degradation by thymidine phosphorylase. Ac2[125I]IUdR and Piv2[125I]IUdR were specifically integrated into the DNA of all tested tumor cell lines but to a less extend than the control [125I]IUdR. In mice, 24 h after i.p. injection, brain radioactivity uptakes were in the following order Piv2[125I]IUdR>Ac2[125I]IUdR>[125I]IUdR. For Ac2[125I]IUdR we detected lower amounts of radioactivities in the thyroid and stomach, suggesting a higher stability toward deiodination. In mice bearing unilateral graft-induced brain tumors, the uptake ratios of tumor-bearing to healthy hemisphere were 51, 68 and 6 for [125I]IUdR, Ac2[125I]IUdR and Piv2[125I]IUdR, respectively. Esterifications of both deoxyribosyl hydroxyl groups of the tumor tracer IUdR lead to advantageous properties regarding uptake into brain tumor tissue and metabolic stability.